Christian hospitality in Javanese bancaan tradition - Panuntun, Daniel F. (HTS teologiese studies, 2021)
Javanese people have unique characteristics and traditions that make them appealing for research. One of the unique things of the Javanese tradition called bancaan is that it is aimed at appreciating children. Bancaan is a simple banquet of gratitude on the occasion of a child’s birthday by inviting their playmates to pray together for their good. This tradition is rich in the value of hospitality but began to disappear as influences of current development overtake. Given this reality, this study discovered Christian values of hospitality in the bancaan tradition. This discovery is based on a survey by Lee Roy Martin and Michele Hersberger. This research is based on the paradigm of qualitative research. Data collection was conducted by examining the literature and studying the Bible. The problem was analysed using interactive analysis, revealing Christian hospitality values in the bancaan tradition. The values showed are as follows: (1) bancaan is open to everyone in nature despite their backgrounds, (2) bancaan is a form of interaction of hospitality in simplicity and (3) bancaan is a form of regeneration of hospitality values to the child.Contribution: This manuscript provided an overview of one form of Javanese culture, which was then linked to the principles of hospitality from Jesus. This culture was a form of Javanese culture towards children’s appreciation. It is hoped that this manuscript contributes to the preservation of Javanese bancaan culture.